Cervical Screening by Pap Test and Visual Inspection Enabling Same-Day Biopsy in Low-Resource, High-Risk Communities. Issue 6 (December 2018) - Tao, Lin; Amanguli, A.; Li, Feng; Wang, Ying Hong; Yang, Lan; Mohemaiti, Meiliguli; Zhao, Jin; Zou, Xiao Guang; Saimaiti, Abudukeyoumu; Abudu, Mirensha; Maimaiti, Mikairemu; Chen, Shi Yan; et al.
Abstract : OBJECTIVE: To develop an effective, low-cost, single-visit cervical screening strategy incorporating a modified Pap test and visual inspection with acetic acid and Lugol's iodine for low-income settings. METHODS: We conducted a prospective cohort trial. Two low-income Muslim Uyghur communities in China's far western Kashi Prefecture served as pilot and validation study sites, respectively, and 4, 049 women (aged 30–59 years) were screened. The conventional Pap test was modified using a cotton swab to collect cervical cells without scraping the cervix using an Ayre spatula, allowing visual inspection with acetic acid (and visual inspection with Lugol's iodine if visual inspection with acetic acid was negative) to be performed in a single visit. Results from both tests were available within 1–2 hours. Women positive for either or both underwent same-day biopsy that was shipped by a courier service to a central pathology laboratory. RESULTS: Single-visit screening incorporating both a modified Pap test and visual inspection achieved a sensitivity of 96.0% (95% CI 91.6–100), which was superior to Pap testing (76%, 95% CI 66.3–85.7; P <.001) or visual inspection with acetic acid–visual inspection with Lugol's iodine (48%, 95% CI 36.7–59.3; P <.001) alone in detecting cervical intraepithelial neoplasia (CIN) 2 or worse lesions. Rapid interpretation of both diagnostic procedures facilitated efficient same-day biopsy that achieved a negative predictive value of 98.2% in detecting CIN 2 or worse lesions. The increased sensitivity and minimized loss of follow-up allowed this approach to identify an extremely high prevalence of CIN 1 (2, 741/100, 000, 95% CI 2, 238–3, 245/100, 000), CIN 2 or 3 (1, 457/100, 000, 95% CI 1, 088–1, 826/100, 000), and cervical cancer (395/100, 000, 95% CI 202–589/100, 000) among these underscreened, at-risk women. CONCLUSION: Single-visit cervical screening with both a modified Pap test and visual inspection has greater sensitivity to detect high-grade CINs, reduces loss of follow-up, and could be an efficient low-cost strategy for low-resource settings. Abstract : Rapid interpretation of a modified Pap test and visual inspection with acetic acid and Lugol's iodine allowing for same-day biopsy is a low-cost approach to efficient cervical cancer screening in a low-resource setting.